2015
DOI: 10.1073/pnas.1508702112
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of the 3-dimensional DNA lesion distribution induced by energetic charged particles in a mouse model tissue

Abstract: Charged particles are increasingly used in cancer radiotherapy and contribute significantly to the natural radiation risk. The difference in the biological effects of high-energy charged particles compared with X-rays or γ-rays is determined largely by the spatial distribution of their energy deposition events. Part of the energy is deposited in a densely ionizing manner in the inner part of the track, with the remainder spread out more sparsely over the outer track region. Our knowledge about the dose distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…These IR-induced DSBs activate ATM and DNA-PK-mediated DNA damage responses (DDR) within seconds to minutes, generating cytologically visible repair foci encompassing hundreds of kilobases of modified chromatin in each direction of the break site that serves to recruit end-processing and DSB repair proteins to restitute the break. 6164 In the case of ∼ 1‐2 high-LET iron ion traversals, nearly all of the energy deposited by their tracks and associated δ-ray penumbras involve more limited nuclear volumes and genomic regions located directly along the particle track 65,66 with much higher local ionization densities and resulting DSBs and clustered lesions. 67 HZE ion-induced DSBs have been shown to be more refractory and slower to repair than low LET IR-induced DSBs, with a greater proportion being preferentially repaired by Rad51-mediated homologous recombinational repair (HRR), 68,69 yielding much higher levels of simple and complex chromosomal rearrangements post irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…These IR-induced DSBs activate ATM and DNA-PK-mediated DNA damage responses (DDR) within seconds to minutes, generating cytologically visible repair foci encompassing hundreds of kilobases of modified chromatin in each direction of the break site that serves to recruit end-processing and DSB repair proteins to restitute the break. 6164 In the case of ∼ 1‐2 high-LET iron ion traversals, nearly all of the energy deposited by their tracks and associated δ-ray penumbras involve more limited nuclear volumes and genomic regions located directly along the particle track 65,66 with much higher local ionization densities and resulting DSBs and clustered lesions. 67 HZE ion-induced DSBs have been shown to be more refractory and slower to repair than low LET IR-induced DSBs, with a greater proportion being preferentially repaired by Rad51-mediated homologous recombinational repair (HRR), 68,69 yielding much higher levels of simple and complex chromosomal rearrangements post irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…X rays are low-LET radiation, which generate DSBs of modest complexity. In contrast, high-LET radiation, such as heavy ions or α particles, induces highly complex DSBs 65 , 66 . Significantly, most DSBs induced by high-LET radiation are repaired with similar kinetics to the X-ray-induced slow DSB repair component 38 , 67 ( Figure 1 B).…”
Section: Chromatin Environment and Damage Complexity Influence Pathwamentioning
confidence: 99%
“…Live cell imaging of protein recruited to the track core has been used by us and others to measure the movement of the DSB lesions in the cell nucleus [13][14][15] . We have previously shown that the yield of heavy ion-induced DSBs as a function of the distance from the primary track can be well described by the physics of the energy deposition of the primary ion and δ-rays 16 . To measure the repair kinetics in single DSB sites we have now exposed to swift heavy ions human osteosarcoma (U2OS) cells stably expressing the GFP-tagged DSB repair factors NBS 17 and 53BP1 18 , two different DSB surrogate markers which were recruited in all cell cycle phases.…”
mentioning
confidence: 99%